Diversity of the Tellurite Resistance Gene Operon in Escherichia coli - Nguyen, Thi Thu Huong; Kikuchi, Taisei; Tokunaga, Tadaaki; Iyoda, Sunao; Iguchi, Atsushi (Frontiers in Microbiology, 2021)
Tellurite is highly toxic to most bacteria owing to its strong oxidative ability. However, some bacteria demonstrate tellurite resistance. In particular, some Escherichia coli strains, including Shiga toxin-producing E. coli O157:H7, are known to be resistant to tellurite. This resistance is involved in ter operon, which is usually located on a prophage-like element of the chromosome. The characteristics of the ter operon have been investigated mainly by genome analysis of pathogenic E. coli; however, the distribution and structural characteristics of the ter operon in other E. coli are almost unknown. To clarify these points, we examined 106 E. coli strains carrying the ter operon from various animals. The draft genomes of 34 representative strains revealed that ter operons were clearly classified into four subtypes, ter-type 1 to 4, at the nucleotide sequence level. Complete genomic sequences revealed that operons belonging to three ter-types (1, 3, and 4) were located on the prophage-like elements on the chromosome, whereas the ter-type 2 operon was located on the IncHI2 plasmid. The positions of the tRNASer, tRNAMet, and tRNAPhe indicated the insertion sites of elements carrying the ter operons. Using the PCR method developed in this study, 106 strains were classified as type 1 (n = 66), 2 (n = 13), 3 (n = 8), and 4 (n = 17), and two strains carried both types 1 and 2. Furthermore, significant differences in the minimum inhibitory concentration (MIC) of tellurite were observed between strains carrying ter-type 4 and the others (p < 0.05). The ter-type was also closely related to the isolation source, with types 2 and 4 associated with chickens and deer, respectively. This study provided new insights related not only to genetic characteristics of the ter operons, but also to phenotypic and ecological characteristics that may be related to the diversity of the operon.